INVENTARISASI JENIS TANAMAN PANGAN BUDIDAYA PADA MASYARAKAT DESA BONTOTANGNGA KECAMATAN BONTOLEMPANGAN KABUPATEN GOWA SULAWESI SELATAN - Sulbi, Aprilia Surani; Amaliah, Rezeki; Liana, Alin (FKIP, Universitas Muslim Maros, 2025)
The background of this research is to add to the completeness of information owned by Bontotangnga Village through inventory data of the types of food plants that are cultivated. Thus the region will have a database of potential food resources to support the acceleration of sustainable food diversification. The purpose of this study was to determine the types of food plants cultivated by the people of Bontotangnga Village. The method used is a survey by conducting observations and interviews. Data collection techniques are equipped with open and closed interviews guided by a list of questions. The data obtained were analyzed descriptively qualitatively and quantitatively. A qualitative approach is used in describing the results of interviews with resource persons. A quantitative approach is used to calculate food crop commodities This study found 32 types of food crops cultivated by the community in Bontotangnga Village (Bontokaru Hamlet, Ompoa Hamlet and Bontomarannu Hamlet). From the results of the LQ (Location Qoutiont) value, there are 11 food crop sectors that are the basis for Bontokura hamlet; 10 sectors of Ompoa hamlet; 13 sectors of Bontomarannu hamlet